2019
DOI: 10.1590/1413-7054201943007219
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose concentration and volume of liquid medium on the in vitro growth and development of blackberry cv. Tupy in temporary immersion systems

Abstract: Micropropagation of small fruits such as blackberry has been employed due to the need to obtain plants with high phytosanitary quality. Bioreactor technology has been used to improve efficiency in seedling production. Thus, the objective of this work was to evaluate the best culture medium volume and sucrose concentration for blackberry micropropagation in a temporary immersion bioreactor. In vitro blackberry shoots were segmented containing two buds and an internode (1.0 cm) and placed into MS medium suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
(12 reference statements)
1
6
0
2
Order By: Relevance
“…Studies performed by Poothong et al (2020) showed that reducing sucrose in MS medium increased the number and length of raspberry buds in culture medium without or with low sucrose concentration. The excess of sucrose in the culture medium can inhibit chlorophyll synthesis and reduce the photosynthetic capacity, which may result in lower carbon gain and dry weight (Ayub et al 2019), as observed in the present study.…”
Section: Resultssupporting
confidence: 67%
“…Studies performed by Poothong et al (2020) showed that reducing sucrose in MS medium increased the number and length of raspberry buds in culture medium without or with low sucrose concentration. The excess of sucrose in the culture medium can inhibit chlorophyll synthesis and reduce the photosynthetic capacity, which may result in lower carbon gain and dry weight (Ayub et al 2019), as observed in the present study.…”
Section: Resultssupporting
confidence: 67%
“…Roels et al 21 and Roels et al 22 stated that 10 ml of medium per explant influenced the shoot multiplication in plantain banana. Ayub et al 32 observed that an optimum volume of culture medium significantly increases shoots per explant in micropropagation of blackberry. Ramos-Castellá et al 33 described that 25 ml of media per explant increases the shoot multiplication in Vanila planifolia.…”
Section: Discussionmentioning
confidence: 99%
“…The least number of shoots were detected in 10 g/L sucrose application (2.2±0.1 shoots/explant). Ayub et al [26] cultured the node and internodes of the blackberry (Rubus spp. L.) in a nutrient environment containing 1 mg/L BAP and 10-40 g/L sucrose and obtained the best regeneration values at a concentration of 20 g/L sucrose.…”
Section: Resultsmentioning
confidence: 99%